Development of E- Comic Education on Anti Drugs Based on Local Wisdom to Foster Character Culture From an Early Age - Abu Anwar; Alfiah Alfiah (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2025)
This study aims to develop a Flipped E-Comic approach for anti-drug education based on students’ local wisdom. The design stage of this approach is the main focus, emphasizing cultural values and students’ local knowledge. This research includes identifying learning objectives that reflect cultural character and anti-drug values, selecting learning content relevant to students’ cultural backgrounds, and developing an E-comic format that integrates cultural elements. It also includes creating an interactive user interface that reflects local cultural features and utilizing visual and multimedia components that support cultural values. The prototype testing stage involved students from diverse cultural backgrounds to collect feedback for further design improvements. The results were used to improve the E-Comic tutorial design to align with the intended learning objectives. This research integrates cultural elements and local wisdom into instructional design, creating a learning tool that that is culturally relevant to students. The study highlights the importance of instructional design that considers cultural and local values in achieving anti-drug education goals. It also demonstrates that the Flipped E-Comic approachcan serve as an effective alternative for promoting cultural character education and raising anti-drug awareness among students from an early age.    Keywords: Anti-Drug Education, Students’ Local Wisdom, E-Comic ABSTRAK. Penelitian ini bertujuan untuk mengembangkan Pendekatan Flipped E-Komik Pendidikan Anti Narkoba berbasis Kearifan Lokal. Tahap desain pendekatan ini menjadi fokus utama dengan memperhatikan nilai-nilai budaya dan kearifan lokal siswa. Penelitian ini mencakup identifikasi tujuan pembelajaran yang mencerminkan karakter budaya dan nilai-nilai anti narkoba, pemilihan konten pembelajaran yang sesuai dengan kearifan lokal siswa, pengembangan format E-Komik yang memadukan elemen-elemen budaya, interaktivitas, desain antarmuka pengguna yang mencerminkan unsur budaya lokal, serta penggunaan media visual dan multimedia yang mendukung nilai-nilai budaya. Tahap pengujian prototipe tutorial E-Komik melibatkan siswa dari beragam latar belakang budaya, dengan tujuan mendapatkan umpan balik yang diperlukan untuk perbaikan desain. Hasil pengujian prototipe digunakan untuk memperbaiki dan menyesuaikan desain tutorial E-Komik agar sesuai dengan tujuan pembelajaran. Penelitian ini mengintegrasikan elemen-elemen budaya dan kearifan lokal dalam desain pembelajaran, menciptakan alat pembelajaran yang sesuai dengan konteks budaya siswa. Penelitian ini menyoroti pentingnya desain pembelajaran yang mempertimbangkan nilai-nilai budaya dan lokal dalam mencapai tujuan pendidikan anti narkoba, serta menunjukkan bahwa pendekatan seperti Flipped E-Komik dapat menjadi alternatif yang efektif dalam pendidikan karakter budaya dan kesadaran anti narkoba pada siswa sejak dini.Kata Kunci : Pendidikan Anti Narkoba, Kearifan Lokal, E- komik